Integrating Quality and Sustainability: Exploring the Dynamics of Internal Quality Assurance Systems and Sustainable Development Goals in Vietnamese Higher Education - Thuy, Tran Thi; Thao, Le Thanh; Thuy, Pham Trut (Journal of Ecohumanism, 2024)
This study explored the integration of internal quality assurance (IQA) systems with sustainable development goals within the Vietnamese academic context, aiming to elucidate the perceptions, experiences, and challenges faced by lecturers. Employing a qualitative methodology, in-depth interviews were conducted with 10 university lecturers, and the data was interpreted through Constructivist Epistemology (CE) and Interpretive Phenomenological Analysis (IPA). Findings underscored the profound influence of collaborative dialogues, leadership dynamics, experiential learning opportunities, and cultural nuances on the melding of IQA processes with sustainability initiatives. Participants highlighted the tension between the prescriptive nature of IQA and the adaptive essence of sustainable development, emphasizing the need for a balanced approach. Furthermore, the role of leadership in shaping institutional narratives emerged as a pivotal factor, with a clear vision and commitment facilitating seamless integration. Cultural factors, unique to the Vietnamese context, either propelled or hindered this fusion, revealing the deep interplay between cultural values and academic practices. The study concluded that while challenges persist, the merging of IQA with sustainable development objectives offers promising avenues for fostering holistic education, grounded in both quality and sustainability. The findings have implications for academic institutions, policymakers, and educators striving to align quality assurance mechanisms with evolving global sustainability objectives.